Digital support for living with and beyond gynaecological cancer. Issue 4 (November 2020) - Ashmore, L.A.; Stewart, H.; Hutton, D.; Evans, K.
Abstract: Introduction: Gynae-Radiotherapy places exceptional psychosocial and physical burdens on patients. Technological developments and associated acute toxicity and survival outcomes have improved, however holistic support has not kept pace. Digital technologies have potential to enhance support and patient experience. The project aimed to co-create a prototype of a digital health intervention that could serve the needs of women living with and beyond treatment for gynaecological cancer. Methods: A multi-disciplinary and co-creation approach was adopted. Four workshops were held, comprising of a number of activities to support participants' expression of views and facilitate discussion. Methods included word cloud generation, prompt cards, empathy maps and persona creation, domain storylines and requirements identification. Results: Support drops off dramatically once treatment is completed. Patients struggled to adjust to their 'new normal' and felt unprepared for changes post-treatment. Patients felt overwhelmed with leaflets yet wanted instant access to reliable and relevant information in one place, better information on late side effects and improved communication about sexual health and sexuality. Reassurance through a digital intervention was viewed positively and specific ideas for achieving this were suggested through: Sharing experiences; targeted practical advice; peer support and advice/support for significant others. Conclusion: The co-creation of a prototype generated further discussion and an interactive prototype was developed. Based on workshop findings it is believed that the intervention could provide life-long support for women living with and beyond cancer. Implications for practice: Increased focus is needed on the late effects of radiotherapy, specifically in supporting psychosocial wellbeing. Co-creation is a rewarding and fulfilling activity that met numerous aims beyond those of the project. It is recommended that mixed staff-patient groups are developed and adopted in more informal ways for the improvement of services.